Patterning, Reading, and Executive Functions - Bock, Allison M.; Cartwright, Kelly B.; McKnight, Patrick E.; Patterson, Allyson B.; Shriver, Amber G.; Leaf, Britney M.; Mohtasham, Mandana K.; Vennergrund, Katherine C.; Pasnak, Robert (Frontiers in Psychology, 2018)
Abstract Detecting a pattern within a sequence of ordered units, defined as patterning, is a cognitive ability that is important in learning mathematics and influential in learning to read. Recent studies have differed in identifying executive functions (EF) that may underlie patterning. The present study was designed to examine relations between first-grade children’s EF, patterning and reading abilities, and to examine whether these relations differ by the type of pattern. The results showed that cognitive flexibility was correlated with overall patterning performance and with performance on object size patterns, whereas working memory was correlated with performance on symmetrical patterns and growing number patterns. This suggests that the cognition required for completing patterns differs depending on the pattern type. Teachers may find it beneficial to place emphasis on the switching and working memory components of completing patterning tasks, depending on the type of patterns used in instruction.